Attention deficit hyperactivity disorder in athletes - Ciocca, M. (Clinics in Sports Medicine, 2019)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder that manifests in difficulties with sustaining attention in tasks and/or hyperactivity/impulsivity. Prevalence rates vary and difficulties in objectively diagnosing ADHD may lead to overdiagnosis or underdiagnosis. Assessment should include a comprehensive evaluation, including history, physical, psychological evaluation, and questionnaires for ADHD. Stimulant medications are effective for treatment, but their use, side effects, and potential for misuse and abuse are a concern, particularly in athletes. Athletes and physicians also need to be aware of the governing body`s drug policy for the sport.